2005
DOI: 10.1088/0022-3727/38/5/014
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Ga2O3/SiC MRISiC devices: a study of the hydrogen response

Abstract: The electrical properties of Pt/Ga2O3/SiC metal oxide semiconductor devices are presented in this paper in order to determine the hydrogen sensing mechanism. This was achieved by studying the role of the interface states upon the introduction of hydrogen/hydrocarbon gas. Current–voltage (I–V), conductance–voltage (C–V) and capacitance–voltage (G–V) experiments have been carried out to investigate the gas sensing mechanism. The devices' hydrogen and propene gas sensitivities were also investigated. This was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This requirement has generated the search for materials capable of working reliably in such severe conditions. Metal-oxide-semiconductor (MOS) 1 and, particularly, metal-reactive insulator-siliconcarbide (MRISiC) 2,3 devices have attracted much interest for their applications in extreme industrial conditions. Moreover, hydrogen sensing is becoming very important because of the possible use of hydrogen as a clean source of energy.…”
Section: Introductionmentioning
confidence: 99%
“…This requirement has generated the search for materials capable of working reliably in such severe conditions. Metal-oxide-semiconductor (MOS) 1 and, particularly, metal-reactive insulator-siliconcarbide (MRISiC) 2,3 devices have attracted much interest for their applications in extreme industrial conditions. Moreover, hydrogen sensing is becoming very important because of the possible use of hydrogen as a clean source of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the magnitude of the barrier height shift increases with the increase of hydrogen concentrations. Trinchi et al [24] have also reported that the barrier height of Pt/Ga 2 O 3 /SiC based hydrogen gas sensors increases with the increase of hydrogen concentrations. …”
Section: B Electrical Propertiesmentioning
confidence: 93%
“…2 The detection system in these sensing materials is usually based on measuring the change in capacitance, work function, mass, optical characteristics or reaction energy released during the gas/solid interaction. 3 But, high working temperature (∼ 400 C) of metal oxide-based CH 4 sensors may easily lead to explode the CH 4 .…”
Section: Recognitionmentioning
confidence: 99%
“…[1][2][3][4] But, among the importance of the detection of various gas analytes, methane (CH 4 has been considered as a major constituent of natural gas due to its widely use in our daily life as prime energy-source material. 1 This phenomenon demonstrates the strong requirement for CH 4 …”
Section: Introductionmentioning
confidence: 99%